The Education of Children Under Seven - Sturt, Mary (Routledge Library Editions: Education, 1932)
This book does not cover the whole field of Infants' Teaching but is concerned mainly with general principles and matters which are open to the non-specialist. Some technical subjects such as Physical Education have been omitted but nonetheless the volume provides a thorough (if somewhat dated) introduction to early years education in the first half of the twentieth century.